Press Law Education for Journalists in Facing the Risks of Digital Criminalization - Syafriadi, Syafriadi; Efendi, Akmar; Santri, Selvi Harvia; Azzahra, Rahima; Parsa, Faizi (AIWADTHU: Jurnal Pengabdian Hukum, 2026)
Introduction: In the digital era, journalists increasingly face the risk of criminalization due to journalistic work interpreted through multi-interpretative provisions of the Electronic Information and Transactions Law and the Criminal Code. This condition creates tension between press freedom as a constitutional function and law enforcement practices that ignore the Press Law as lex specialis.Purposes of The Devotion: The purpose of this article is to provide legal education for journalists to strengthen their understanding of press law and reduce the risk of digital criminalization in journalistic practices.Method of The Devotion: This community service activity employed legal education methods through lectures, discussions, and case studies involving journalists to enhance awareness of press freedom, social responsibility, and press dispute resolution mechanisms.Results Main Findings of the Devotion: The results of the community service activity indicate an increase in journalists’ understanding and legal awareness regarding the balance between press freedom and social responsibility in carrying out the journalistic profession. Participants gained a more comprehensive understanding of the risks of digital criminalization, particularly those arising from the application of multi-interpretable provisions in the Electronic Information and Transactions Law (UU ITE). In addition, this activity encouraged journalists to implement preventive measures through the strengthening of journalistic ethics, fact verification, and compliance with the principles of press law.